Distributed energy strategy using renewable energy transformation in Kinmen Island: Virtual power plants that take the military camps as the mainstay. (November 2022) - Lee, Hsi-Chieh; Liu, Hua-Yueh; Teng, Sheng-Yuan
Abstract: Kinmen island, also known as Quemoy island, is a famous Cold War island on the west side of Taiwan strait which is less than 2 km away from China but under the governance of Taiwan that is 210 km away. The geographical location and political issues make Kinmen a typical island with isolated power grids. Considering Taiwan's 2025 green-energy penetration rate goal of 20%, the implementation of Kinmen Low-Carbon Island 2.0, and transformation of idle military camps into energy-oriented utilizations, this study focuses on employing Kinmen Island's natural resources. Peak sun-hours and military camps are utilized to develop a virtual power plant based on renewable energy, where the resulting distributed energy strategy reduces the demand for fuel oil in existing centralized power plants. The proposed energy management system regulates an energy storage system to compensate for the intermittent power fluctuations of renewable energy at the power-generation end, reducing the burden of backup capacity and balancing the overall power system. This study proposes a customized framework for connecting, transforming, and developing military facilities for Kinmen island to move toward a low carbon island. Evaluation by this study illustrates Kinmen island is capable of achieving 50% renewable energy by building an average of 127.22 kW PV in each of the 850 military camp. And by building an average of 276.47 kW PV in each of the 850 military camp, the goal of 100% renewable energy if also feasible. Highlights: Distributed Energy Transformation Strategy on the Famous Cold War Island: Kinmen. 850 Military Camps to be Utilized to Develop Virtual Power Plants. Analysis of the Amount for PVs and Wind Turbines in each Military Camp. The Concept of "Peace Closure and War Activating" for the Camp-based VPPs. Virtual Power Plants that Take the Military Camps as the Mainstay.